Pre-service Teacher Beliefs on the Antecedents to Bullying: A Concept Mapping Study - Lopata, Joel; Nowicki, Elizabeth A. (Canadian Journal of Education/Revue canadienne de l’éducation, 2014)
In this study, researchers gathered Canadian pre-service teachers’ beliefs on the antecedents to bullying. Concept mapping (Kane & Trochim, 2007) was used to analyze the data. This study’s findings identified pre-service teachers to have accurate beliefs, inaccurate beliefs, and a lack of knowledge about the antecedents to bullying. Concept maps and accompanying factor-rating tables indicate that participants believe antecedents to bullying include family factors, abuse, instability and socio-economic factors, school and academic factors, interpersonal factors, and personal factors. Results may inform pre-service teachers’ knowledge, and indicate what information pre-service teachers need to be taught.